Social capital and support for the welfare state in Russia. Issue 5 (3rd September 2017) - Borisova, Ekaterina; Govorun, Andrei; Ivanov, Denis
Abstract: Few tasks are more important in a post-communist setting than rebuilding the welfare state. We study individual preferences for increasing social welfare spending to reduce inequality. Using two surveys of about 34, 000 and 37, 000 Russians, we show the great importance of the "bridging" type of social capital for redistribution preferences in Russia, as it precludes possibilities of cheating and free-riding on the welfare state. Instrumenting social capital with education, climate, and distance from Moscow, we deal with endogeneity concerns and also contribute to our understanding of the deep roots of social capital in Russia. We claim that social capital in post-socialist countries could help mobilize public support for redistribution even where institutions are weak.